Retrospective Cohort Study of Intraoperative Administration of Sustained-Release 5-Fluorouracil Implants in Advanced Gastric Cancer Patients - Ge, Jie; Liu, Ting; Lei, Tianxiang; Li, Xuan; Song, Kun; Azizi, Samim; Liu, Heli; Tang, Mimi (Frontiers in Pharmacology, 2021)
Background: 5-fluorouracil (5-FU) is basically used in the field of postoperative chemotherapy of gastric cancer (GC), the goal of this study was to evaluate improvement of long-term survival rate among GC patients after the 5-FU implants treatment. Methods: The study included 145 patients with gastric cancer who received postoperative chemotherapy with 5-FU implants and had complete follow-up information. According to the sex, age and clinical stage of 5-FU implants group, 74 patients were matched as the control group at the same time. In the study, we compared the 5-year survival rate with progression-free survival rate in the two groups, and the drug safety for both groups during the treatment was also compared. Results: The median follow-up time was 85 months (range 60-116 months). 31 patients (21.38%) died of tumor recurrence in 5-FU implants group and 21 (28.38%) in control group. In the control group, metastatic lesions were found in the small intestine, left adrenal gland and peritoneum in three patients. The 5-year progression-free survival (PFS) rate was 79.71% in 5-FU group and 67.12% in control (P = 0.0045). The 5-year overall survival (OS) rate were 77.68% in 5-FU implants group and 64.87% in control (P=0.0159). Both the 5-year OS and PFS in 5-FU group were better than control group without significant side effect. Conclusion: 5-FU implants may improve 5-year OS and PFS after surgery in gastric cancer patients, while good safety profile suggests it could be reliable.